The Role of Moral Intelligence of Internal Auditors in Support of the Performance of Internal Audit Process - Study for Opinions of a Sample of Internal Auditors in Iraq - رشيد ناظم حسن (Journal of Economics and Administrative Sciences, 2016)
Abstract The aim of the research to define the concept of moral intelligence and its dimensions and its relationship to some personal characteristics with the internal auditors and identify the importance of the employment of moral intelligence dimensions of (empathy, conscience, self- control, respect, kindness, tolerance, fairness) in the internal audit and the extent of support for the performance of the internal audit process in light of these dimensions. And that by answering the following question : Is there a role for moral intelligence of internal auditors in support the performance of internal audit process ? How are employ these dimensions in support the performance of the internal audit process ? The research has reached to the list of results, The most important that there is a role of moral intelligence of internal auditors in support of the performance of the internal audit process through the promotion of internal auditors to respect their obligation to the laws and instill confidence in dealing with others treat them friendly and respectful on the justice basis away from the bias in different positions.